Lignocellulosic biomass pre-treatment using low-cost ionic liquid for bioethanol production: An economically viable method for wheat straw fractionation. (August 2021) - Ziaei-Rad, Zhila; Fooladi, Jamshid; Pazouki, Mohammad; Gummadi, Sathyanarayana N.
Abstract: Low-cost Ionic Liquid (IL) is a promising method for the lignocellulosic biomass pretreatment to produce bioethanol. This study investigates utilizing low-cost IL, [TEA][HSO4 ], for wheat straw pretreatment. The pretreatment was investigated in conditions characterized by a temperature of 130 °C, a high solid-to-solvent load ratio of 1:5 g/g, and 20 wt % water to separate lignin and carbohydrates from the source, which would subsequently undergo enzymatic hydrolysis. The highest delignification rate of 80% and the hemicellulose removal rate of 64.45% were observed in the case of a 3-h pretreated sample with [TEA][HSO4 ]. Two biomass samples pretreated for 0.5 h and 3-h showed high glucose saccharification yield levels of 50.36 and 87.19%, respectively, and 78.23% xylose yield was achieved in 3-h pretreated sample in enzymatic hydrolysis with commercial enzyme CelluMax in 72 h. Ethanol production and yield of 3-h pretreated biomass reached 43.1 g/L and 84.34% of the maximum theoretical yield after 48 h of fermentation time. However, the yield of the untreated biomass was only 10.76%. Obtained results clearly demonstrated that pretreatment with low-cost IL prior to enzymatic hydrolysis led to higher ethanol yield due to successful delignification. The process developed in this study exhibited economic feasibility of this technique in industrial bioprocess. Graphical abstract: Image 1 Highlights: An effective pretreatment method using Low-cost Ionic Liquid was developed. 80% delignification and 64% hemicellulose removal was achieved at high biomass loading. Glucose and xylose yields of 87 and 78% was obtained using a commercial cellulase. High ethanol yield of 84% was observed in 48 h fermentation. [TEA][HSO4 ] is cost effective solvent for wheat straw fractionation.